Use of early-TIPS for high-risk variceal bleeding: Results of a post-RCT surveillance study - Garcia-Pagán, Juan Carlos; Pascoli, Marco Di; Caca, Karel; Laleman, Wim; Bureau, Cristophe; Appenrodt, Beate; Luca, Angelo; Zipprich, Alexander; Abraldes, Juan G.; Nevens, Frederik; Vinel, Jean Pierre; Sauerbruch, Tilman; et al. (Journal of hepatology, 2013)
Liver cirrhosis; Portal hypertension; Prognosis; Treatment